Risk factors for relapse in pediatric nephrotic syndrome - Husein Albar; Fadel Bilondatu; Dasril Daud (Indonesian Pediatric Society, 2018)
Background Nephrotic syndrome (NS) is the most common kidney disease in children and is characterized by edema, massive proteinuria, hypoalbuminemia, and hyperlipidemia. High relapse rate remains a major problem in the management of this syndrome. Objective To identify risk factors for relapse in pediatric nephrotic syndrome. Methods This study was carried out in the Wahidin Sudirohusodo Teaching Hospital in Makassar, South Sulawesi, Indonesia, from January to August 2017 using complete medical records of children diagnosed with NS. Subjects were divided into 2 groups: 1) relapsed NS or 2) non-relapsed NS. The following potential risk factors for relapse were analyzed using Chi-square test: age, sex, nutritional status, hypertension, serum creatinine level, and infection at the time of established diagnosis of NS. Results A total of 142 children with NS who fulfilled the inclusion criteria aged 1.4 to 17.5 years were included in the study. Subjects were mostly boys (66.2%), with a male: female ratio of 1.95:1. The relapsed NS group had 80 cases (56.3%) and the non-relapsed NS group had 62 cases (43.7%). Statistical analysis revealed that nutritional status was a significant risk factor for relapse in pediatric nephrotic syndrome (P<0.05). Conclusion Nutritional status is an independent risk factor for relapse in pediatric nephrotic syndrome.